The humanism of Dante - Bowers, John Leslie (Department of Philosophy, 2016)
Humanism may be defined as the ethic of human nobility. As such, it is largely associated with the Renaissance, which discovered anew the civilization of Greece and Rome. Yet, Mediaeval culture was also deeply influenced by Classical ideals, and it is part of our task to make some distinction between the Mediaeval and Classical attitudes. Dante's profound admiration for the ancient world is evident throughout his writings and goes far beyond anything which can be regarded as the general view of the Middle Ages. It is the task of this essay to examine the nature of this influence of the Classical past, to trace its development in poetry, in philosophy, in theology. This requires an investigation into the nature of the early Humanism of the "Convivio", which we have studied at some length because of its importance in the evolution of the poet's thought. The "Convivio" is philosophical in intention, rational in method, Aristotelian in sympathy. It is, however, coloured by Christian idealism, despite its Stoic and, indeed, Pelagian tendency.